2013
DOI: 10.1038/ismej.2013.90
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of pathogenic lineages of Vibrio nigripulchritudo identifies virulence-associated traits

Abstract: Vibrio nigripulchritudo is an emerging pathogen of farmed shrimp in New Caledonia and other regions in the Indo-Pacific. The molecular determinants of V. nigripulchritudo pathogenicity are unknown; however, molecular epidemiological studies have suggested that pathogenicity is linked to particular lineages. Here, we performed high-throughput sequencing-based comparative genome analysis of 16 V. nigripulchritudo strains to explore the genomic diversity and evolutionary history of pathogen-containing lineages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…6a). For this, we selected the ExoY-like module from the MARTX toxin encoded by the virulence-associated plasmid pA SFn1 from V. nigripulchritudo 1633, an emerging marine pathogen infecting farmed shrimps. The multidomain MARTX toxin is processed inside host cells into individual effector domains by an inbuilt cysteine protein domain34.…”
Section: Resultsmentioning
confidence: 99%
“…6a). For this, we selected the ExoY-like module from the MARTX toxin encoded by the virulence-associated plasmid pA SFn1 from V. nigripulchritudo 1633, an emerging marine pathogen infecting farmed shrimps. The multidomain MARTX toxin is processed inside host cells into individual effector domains by an inbuilt cysteine protein domain34.…”
Section: Resultsmentioning
confidence: 99%
“…During the warm and cold seasons, two types of vibriosis induce shrimp mortalities in growing ponds, threatening the economic viability of the industry. Epidemiological studies have revealed that the first type of vibriosis results from the highly pathogenic (HP) Vibrio nigripulchritudo (Vn) strain and that the colonization of the shrimp pond ecosystem by this particular pathogenic cluster occurs at the onset of the disease outbreak (Goarant et al, 2006a(Goarant et al, , 2006bReynaud et al, 2008;Le Roux et al, 2010;Goudenège et al, 2013). Known as "Summer Syndrome", this disease is currently restricted to one particular area of New Caledonia (St Vincent Bay).…”
Section: Introductionmentioning
confidence: 99%
“…7a). For this, we selected the ExoY-like module from the MARTX toxin encoded by the virulence-associated plasmid pAs Fn1 from Vibrio nigripulchritudo 13, 31 , an emerging marine pathogen infecting farmed shrimps. The multidomain MARTX toxin is processed inside host cells by an inbuilt cysteine protein domain (CPD), into individual effector domains 32 .…”
Section: Resultsmentioning
confidence: 99%